2024
DOI: 10.1038/s41380-024-02408-9
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine neuron degeneration in the Ventral Tegmental Area causes hippocampal hyperexcitability in experimental Alzheimer’s Disease

Elena Spoleti,
Livia La Barbera,
Emma Cauzzi
et al.

Abstract: Early and progressive dysfunctions of the dopaminergic system from the Ventral Tegmental Area (VTA) have been described in Alzheimer’s Disease (AD). During the long pre-symptomatic phase, alterations in the function of Parvalbumin interneurons (PV-INs) are also observed, resulting in cortical hyperexcitability represented by subclinical epilepsy and aberrant gamma-oscillations. However, it is unknown whether the dopaminergic deficits contribute to brain hyperexcitability in AD. Here, using the Tg2576 mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…In vivo, the sub-chronic treatment of L-DOPA ameliorates hippocampal hyperexcitability by reducing the amplitude of PSs (as proved also by a recent work ;Spoleti et al, 2024); likewise, stimulation of the VTA was found to decrease epileptic activity in hippocampus-kindled mice (Ahmadi et al, 2024).…”
supporting
confidence: 54%
“…In vivo, the sub-chronic treatment of L-DOPA ameliorates hippocampal hyperexcitability by reducing the amplitude of PSs (as proved also by a recent work ;Spoleti et al, 2024); likewise, stimulation of the VTA was found to decrease epileptic activity in hippocampus-kindled mice (Ahmadi et al, 2024).…”
supporting
confidence: 54%
“…35 In the AD brain, Ab plaques were identified to induce dopaminergic degeneration in the ventral tegmental area (VTA). 36 Interestingly, dopamine treatment was found to restore synaptic plasticity and memory cognition in the AD model. Mechanistically, studies have shown that dopamine, and L-Dopa, not only inhibit Ab aggregation but also dissolve the preformed aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Besides GABAergic and glutamatergic synapses [20,28,40], other types of synapses have not been shown, to our best knowledge, to populate PNN meshes. Hippocampal PV+ interneurons receive dopaminergic innervation from ventral tegmental area (VTA) and the firing rate was reduced significantly in those neurons upon VTA dopamine neuron degeneration in the TG2576 mouse model of AD [161]. Futhermore, cortical PV+ interneurons exhibit an abnormal PNN structure, altered action potentials, and deficits in dopaminergic modulation in mice carrying a truncated allele disrupted in schizophrenia allele [162].…”
Section: The Mesh 3d Thicknessmentioning
confidence: 99%